Simulation of a three probe reflectometer system / Nor Wahidah Misran - Misran, Nor Wahidah (2009)
The aim of this project is to do a simulation of a three probe reflectometer system. A slotted line is used to measure three standing wave voltages corresponding to three probe positions which are one-eight wavelengths apart. The output of this measurement can be used for obtaining the complex reflection coefficient of a material. This involves designing a circuit of transmission line measurement using Genesys software. This simulation can later be used to transform the existing bulky three probe reflectometer hardware onto a microstrip. The existing hardware consists of a Gunn diode source, 1 kHz modulator, attenuater, slotted line, A/D converter and a computer. Using software, it transforms the existing measurement system known as Reflectometer to Microstrip circuit. The simulation results and published data from Reflectometer measurement system are compared. The microstrip circuit was fabricated and the Reflectometer measurement system becomes smaller and portable.